The Head-Toes-Knees-Shoulders Revised: Links to Academic Outcomes and Measures of EF in Young Children - McClelland, Megan M.; Gonzales, Christopher R.; Cameron, Claire E.; Geldhof, G. John; Bowles, Ryan P.; Nancarrow, Alexandra F.; Merculief, Alexis; Tracy, Alexis (Frontiers in Psychology, 2021)
The measurement of self-regulation in young children has been a topic of great interest as researchers and practitioners work to help ensure that children have the skills they need to succeed as they start school. The present study examined how a revised version of a commonly used measure of behavioral self-regulation, the Head-Toes-Knees-Shoulders task (HTKS) called the HTKS-R, and measures of executive function (EF) were related to academic outcomes between preschool and kindergarten (ages 4-6 years) in a diverse sample of children from families with low income participating in Head Start in the United States. Participants included 318 children (53% female; 76% White; 20% Latino/Hispanic) from 64 classrooms in 18 Head Start preschools who were followed over four time points between the fall of preschool and the spring of kindergarten. Results indicated that children with higher HTKS-R scores had significantly higher math and literacy scores at all time points between preschool and kindergarten. The HTKS-R was also a more consistent predictor of math and literacy than individual EF measures assessing inhibitory control, working memory, and cognitive flexibility. Parallel process growth models indicated that children who had high initial scores on the HTKS-R also had relatively higher initial scores on math and literacy. In addition, growth in children’s scores on the HTKS-R across the preschool and kindergarten years was related to growth in both children’s math and literacy scores over the same period independent of their starting points on either measure. For the HTKS-R and math, children’s initial scores were negatively associated with growth over the preschool and kindergarten years indicating that lower skilled children at the start of preschool started to catch up to their more skilled peers by the end of kindergarten.